Software Development For Optimal Portfolio Selection Using The Markowitz Method - Nurika Restuningdiah; Makaryanawati Makaryanawati; Aulia Azzardina (International Journal of Accounting and Finance in Asia Pasific (IJAFAP), 2023)
Investors could invest their funds in a collection of financial assets (portfolio). The optimal combination of the portfolio will optimize the return. The purpose of this research is to develop software that supports investment decisions using the model of Markowitz. The method used in developing this software is the System Development Life Cycle method, where in this method there are three stages of system development, namely the Definition Stage, the Construction Stage, and the Implementation Stage. The result of this development is software that can be used to determine the optimal portfolio. The software will support the decision-making of the investment. The output of this research is software, that is validated by expert judgment.